The problem of defining the vocabulary of teaching Arabic language methodology in media colleges - Al-Rubaie, Akram Faraj (ALBAHITH ALALAMI, 2020)
This study examined the problem of identifying the vocabulary of the methodology of teaching Arabic language in the faculties of Media. The researcher noticed the existence of an overlap between the syllabuses of the general specialization of the Arabic language and its Media sections in the universities with the special professional vocabulary that suits the study of the media student. Thus ,this study is regarded as a real attempt to present a methodological model of media language that concerns with fillfuling students ‘linguistic and knowledgeable needs relying on measuring their benefits from the methodological Arabic curriculum .  Key words:problem,  teaching’ methodology of Arabic language, media language.